125th Anniversary Review: Developments in brewing and distilling yeast strains. Issue 4 (13th November 2013) - Stewart, Graham G.; Hill, Annie E.; Russell, Inge
<x xml:space="preserve">Abstract</x> Progress during the past 25 years regarding our knowledge of brewer's yeast strains is considered. This is not a comprehensive review but rather focuses on some specific areas. These areas include a brief description of genomics, proteomics and metabolomics as applied to brewer's yeast strains. This review subsequently considers differences between ale and lager yeast strains, the uptake and metabolism of wort sugars and amino acids, yeast flocculation, yeast management between fermentations and yeast strain genetic stability. The question of process intensification, with particular attention to high‐gravity brewing, is also addressed. Fermentation systems and processes are considered with an emphasis on novel procedures for stirred fermentations. Copyright © 2013 The Institute of Brewing & Distilling